Vitis vini fera sylvestris i vitis vinifera sativa. Udomowienie i upowszechnienie się uprawy winorośli w starym świecie na podstawie badań archeologicznych i paleobotanicznych - Góralczyk, Agnieszka (Folia Praehistorica Posnaniensia, 2016)
This paper looks at the domestication and spread of viticulture in the Old World and shows how useful is botanical research on the contemporary species of wild and cultivated vine for archaeology the paper presents the objectives and possibilities of archaeobotanical research.